PENERAPAN AKAD PEMBIAYAAN MURABAHAH PADA BUMDESA SYARIAH KEMBANG SETANJUNG DESA TANJUNG MEDAN KECAMATAN TAMBUSAI UTARA KABUPATEN ROKAN HULU - Syukri Rosadi (HUKUMAH: Jurnal Hukum Islam, 2022)
ABSTRAKThis study aims to determine the application of murabahah transaction financing to the Syariah BUMDesa Bunga Tanjung. This study also explains the implementation of sharia transactions in the community to find out the understanding and interest of the community to become a Sharia BUMDes customer with sharia principles. The method used in this research is descriptive qualitative method with secondary and primary data. The collection of supporting data is carried out by field studies through interviews, observations and documentation. BUMDes is an instrument that drives the macro economy at the village level based on local potential and local wisdom. Professional management of BUMDes can be a solution in order to promote and prosper all elements of the village community. BUMDes Syariah Bunga Tanjung is a BUMDes in Tanjung Medan Village which has business activities in the form of buying and selling and laying chickens. The author concludes that the application of the murabahah financing contract is a solution from the Syariah BUMDes Bunga Tanjung. The results of this study indicate that the application of murabahah financing contracts on sharia BUMDes transactions in accordance with the Fatwa of the MUI DSN, gives results in the form of  implementing Sharia contracts according to the type of financing product applied to sharia BUMDes Bunga Tanjung.